2014
DOI: 10.4314/thrb.v16i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic bowel obstruction: aetiology, clinical presentation, management and outcome at Bugando Medical Centre, Mwanza, Tanzania

Abstract: Dynamic bowel obstruction is a common and potentially dangerous surgical emergency with high morbidity and mortality worldwide. No prospective study has been done on this subject in our setting. This study was conducted to describe in our region, the aetiology, clinical presentation, management and outcome of dynamic bowel obstruction. Data were analyzed using SPSS software system. A total of 342 patients were studied. Males outnumbered females by a ratio of 2.1: 1. The median age of patients at presentation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
7
6
0
Order By: Relevance
“…7 In Chalya et al, study male to female ratio was 2:1. 10 In present study male to female ratio is 2:1 and comparable to above two studies ( Table 6). In the present study of 50 cases of acute intestinal obstruction 36% of the cases are due to post-operative adhesions who has undergone previous surgeries.…”
Section: Age Incidencesupporting
confidence: 91%
“…7 In Chalya et al, study male to female ratio was 2:1. 10 In present study male to female ratio is 2:1 and comparable to above two studies ( Table 6). In the present study of 50 cases of acute intestinal obstruction 36% of the cases are due to post-operative adhesions who has undergone previous surgeries.…”
Section: Age Incidencesupporting
confidence: 91%
“…Almost all patients had abdominal pain (96%) and abdominal distention (81%). Similar to a Tanzanian study by Chalya et al, it was found that abdominal pain was the main clinical presentation; hospital stay in Chalya et al study was 26 days, which was greater than the median duration of hospital stay in our study of 7.8 (IQR, 8.4 days) [16]. In our study, the most common finding at surgery was gut perforation 30.64% and this consistently agreed with findings from studies done by Clark et al in South Africa [17], Weledji et al from Nigeria [18], and Nandyala et al from India (10) where the most common finding was gut perforation presenting in 30% of patients.…”
Section: Clinical Findings and Findings At Surgery Among Study Patientssupporting
confidence: 88%
“…There is also an increase in incidence of malignant bowel obstruction, as reflected by our study. The most common cause of intestinal obstruction in Phillipo et al [9] study is obstructed hernia, which could be because of either a greater prevalence of intestinal obstruction in that part of the world or due to lower frequency of surgical treatment of uncomplicated hernias, leading to obstruction and other complications. Preventive measures for reducing the burden of colorectal cancer in both low-and high-resource countries include being physically active, maintaining a healthy body weight, minimizing consumption of red meat and alcohol, maximizing consumption of fruit and vegetables, and cessation of smoking.…”
Section: Discussionmentioning
confidence: 93%
“…The overall mean duration of hospitalization in the present study was 13 days. Chalya PL et al [9] study was found 26 days, Markogiannakis H et al [7] study was 7 days. The duration of hospital stay reflects the morbidity due to postoperative complications, with moribund patients requiring longer duration of hospital stay, and early discharge in…”
Section: Duration Of Hospitalizationmentioning
confidence: 92%